Attitudes of general practitioners to presymptomatic testing for Huntington's disease. - Mennie, M E (1990)
A postal questionnaire was sent to all 797 general practitioners (GPs) in the Lothians, Borders, and Fife (Scotland), enquiring about attitudes to presymptomatic testing for Huntington's disease. The response rate was 74%. Eighty-two percent were in favour of the principle of predictive testing for Huntington's disease. A majority of those not in favour were prepared to refer their patients for testing. However, three-quarters of GPs were unfamiliar with the details of DNA based linkage analysis. Half of the respondents felt that disclosure of the test result and subsequent counselling and support were the responsibility of the genetic clinic. A third of respondents considered that the genetic clinic should disclose the test result while the GP should give post-test counselling and support. These findings suggest that delivering presymptomatic testing to persons at risk of Huntington's disease would be facilitated by a closer involvement of local GPs.